MOLECULAR DIAGNOSIS AND PHYLOGENETIC ANALYSIS OF BABESIA SPECIES ISOLATED FROM TICKS OF INFESTED CATTLE IN WASIT GOVERNORATE, IRAQ - & Al-Amery, Al-Abedi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The aim of current study is to detect Babesia bovis, B. bigemina, and B. divergens in ticks using molecular polymerase chain reaction (PCR) assay. In a totally 180 cattle examined to collect of tick samples during December 2018 to August 2019, the findings were revealed on 63 (35%) cattle infested with ticks that classified morphologically to belong to the genus of Hyalomma and genus of Rhipicephalus. From 50 tick samples tested by PCR assay, 41 (82%) were infested by Babesia genus including 30 (68.18%) infested with B. bovis and 11 (31.82%) infested with B. bigemina; whereas, no tick samples were found to be infested with B. divergens. To document the local isolated strains, five PCR products of each B. bovis and B. bigemina positive strains were selected, sequenced and reported in the NCBI under the accession numbers of (MN727083.1, MN727084.1, MN727085.1, MN727086.1, and MN727087.1) and (MN741113.1, MN741114.1, MN741115.1,MN741116.1, and MN741117.1) respectively.